Self Management For Adolescents With Emotion Control - Kurniawati, Asyri Tri; Sholikhah, Siti; Saifudin, Moh.; Susanti, Inta; Ubudiyah, Masunatul; Suhariyati, Suhariyati; Prihatama, Rizky Putra (Jurnal Surya, 2024)
Introduction: Emotional problems are conditions where someone experiences psychological distress and psychological change. Although it can recover, the emotional problems can get worse if they are not treated properly. The research aimed to investigate the effect of self-management therapy on emotional control in adolescents in Tuban Regency Methods: The research applied pre-experimental one group pre-test-posttest design. The population was 39 respondents and used simple random sampling. The data were gathered by using questionnaire sheet. statistic test used Wilcoxon test Results: The research results indicated that before self-management therapy was administered, 31 adolescents (79.5%) experienced high/abnormal emotions and 1 adolescent (2.6%) experienced low/normal emotions. After the therapy was administered, 34 adolescents (87.2) experienced low/normal emotions and only 1 adolescent (2.6%) experienced high/abnormal emotions. The data which were analyzed by the Wilcoxon test indicated significance value of p=<0.05 and the significance value of self-management therapy was p=0.000, meaning that there was an effect of self-management therapy on emotional control in adolescents Conclusion: To control emotional problems in adolescents, one of the alternatives is by providing self-management therapy Keywords: Adolescents,  Emotional control, Self-management therapy